Sistem. Pendukung. Keputusan. Pemilihan. Unit Kendaraan Bermotor Dengan Metode Simple. Additve. Weighting (SAW) - Fathul Ghina; Reza Alif Anugrah; Dwi Nur Febrianto; Munandar Munandar; Perani Rosyani (CV. Multi Kreasi Media, 2022)
A motor vehicle is one of the. most effective and efficient means of transportation. The current increase in total motor products gives the consumer the option of buying the right one and according to his wants, needs and abilities. The purpose of this study is to create a design system for favoring motor-product decisions using the simple, equtive, (SAW) method. The system that supports this decision compares only to 3 Honda products, yamaha and suzuki. Subject research conducted in the city district of tangerang. As a result of this study, the system that supports the decision made by the simple standard-saw method that makes it easier for users to run the best motorcycle decision support system and supports the decision of those who purchase motors in preference to the desired criteria.